Brief Report: Frailty and HIV Disease Severity Synergistically Increase Risk of HIV-Associated Neurocognitive Disorders. (15th August 2020) - Sun-Suslow, Ni; Paolillo, Emily W.; Morgan, Erin E.; Letendre, Scott; Iudicello, Jennifer; Moore, David J.
Abstract : Background: Frailty disproportionally affects people with HIV (PWH) and increased frailty in this already vulnerable population is associated with worse neurocognitive functioning. Whether frailty interacts with current and modifiable markers of HIV disease severity to synergistically increase risk for HIV-associated neurocognitive disorders (HAND), however, is unknown and important for informing the clinical care of aging PWH. Setting: UC San Diego's HIV Neurobehavioral Research Program. Methods: Participants were 178 PWH evaluated between 2014 and 2019. HIV disease severity was measured by current CD4 count and plasma HIV RNA. HAND diagnoses were made according to the Frascati criteria using a 7-domain neuropsychological battery, and the Fried phenotype criteria were used to assess frailty syndrome (0–5 symptoms). The independent and interactive effects of frailty and current HIV disease severity (ie, CD4 count and plasma HIV RNA) on HAND were examined using multiple logistic regressions. Results: There was an interaction between CD4 count and frailty on HAND. Simple slopes showed that CD4 count and the likelihood of HAND were negatively associated at >1.25 symptoms of frailty, and conversely, frailty and HAND were negatively associated at 642 or less cells/mm 3 . There were no significant independent or interactive effects of plasma HIV RNA and frailty on the likelihood of HAND. Conclusions: In addition to monitoring CD4 count, assessing for frailty may be critical in older adults with HIV to potentially mitigate poor neurobehavioral outcomes. Longitudinal follow-up studies are needed to determine the directionality of these findings.